Immune cell senescence in autoimmunity: implications for disease pathogenesis and therapeutic targeting - Yin, Fei; He, Yangfang; Li, Jian; Gao, Yuan (Frontiers in Immunology, 2025)
The senescence of immune cells has also emerged as a key hallmark of immunological dysregulation and chronic inflammation in autoimmunity. Senescent immune cells are irreversibly arrested in the cell cycle, exhibit antimetabolic characteristics, and secrete pro-inflammatory mediators, all together disrupting immune homeostasis. T cells, B cells, and innate immune subsets, acquire a senescence-associated secretory phenotype (SASP), which initiates tissue damage and sustains continuous inflammation in autoimmune diseases. The accumulation of senescent immune cells undermines immune surveillance, disrupts self-tolerance mechanisms, and enhances autoantibody production, all of which contribute to the pathogenesis of autoimmune diseases, including type 1 diabetes (T1D), systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA). Accumulating evidence reveals that metabolic stress, chronic DNA damage, and persistent antigenic exposure in inflammatory microenvironments induce immune cell senescence. Such senescent condition more aggressively promotes disease pathogenesis by compromising antigen presentation, disrupting cytokine signaling, and weakening the function of regulatory T cells (Tregs). Targets of senolytic drugs, SASP inhibitors, monoclonal antibodies (mAbs), and CAR T cell therapy currently have the potential to accelerate autoimmune pathology. These treatments would be directed specifically against the selective elimination or reprogramming of senescent cells to restore immune homeostasis. This review examines the mechanistic relationships between autoimmune development and immune cell senescence, as well as recent advancements in senescence-directed therapy. Understanding these pathways can provide new insights into autoimmune pathogenesis and inform future therapeutic approaches to immune cell aging.